Commercial protectionism as a response to the globalization crisis in the West: Trump and Brexit - Medina Rivas Plata, Anthony Rolando (Universidad Hemisferios, 2024)
In recent years, we have witnessed a significant turn towards commercial protectionism as a response to what some perceive as clear discontent provoked by the current process of globalization. Our work will focus on two of the most emblematic events symbolizing this trend: the presidency of Donald J. Trump (2017-2021) in the United States and the Brexit referendum in the United Kingdom. Trump marked a turning point in U.S. trade policy, advocating an